Perovskite solar cell and preparation method thereof

By adding glutathione to the perovskite precursor solution, it affects the nucleation and crystallization of perovskite crystals, solves the problem of decomposition of perovskite solar cells under environmental influence, and improves their stability and photovoltaic efficiency.

CN118870943BActive Publication Date: 2025-01-21HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411367753.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-21
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Perovskite solar cells are easily decomposed under the influence of humidity, light, heat and other environments, and have poor stability, which limits their commercial applications.

Method used

Adding glutathione to the perovskite precursor solution improves the stability and photoelectric properties of the perovskite active layer by affecting the nucleation process and crystallization orientation of organic-inorganic hybrid perovskite crystals.

Benefits of technology

It improves the stability and photoelectric efficiency of perovskite solar cells, reduces crystal degradation caused by environmental factors such as humidity, light, and heat, and enhances the self-healing ability of the active layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118870943B_ABST
    Figure CN118870943B_ABST
Patent Text Reader

Abstract

The present application relates to the field of new energy technology, and in particular to a perovskite solar cell and a method for preparing the same. The method for preparing the perovskite solar cell comprises the following steps: forming a nickel oxide film on a transparent conductive glass; forming a self-assembled monolayer on the nickel oxide film; mixing glutathione, a perovskite material and an organic solvent to obtain a perovskite precursor solution; coating the perovskite precursor solution on the self-assembled monolayer to form a modified perovskite active layer; forming an electron transport layer on the modified perovskite active layer; and forming an electrode on the electron transport layer. The method of the present application can improve the photoelectric efficiency and stability of perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a perovskite solar cell and a preparation method thereof. Background Art

[0002] In the social context of energy shortage, climate change and environmental pollution, people's demand for renewable energy is increasing. As a stable energy supplier among renewable energy sources, solar energy has become a research hotspot pursued by scientific research institutions and high-tech enterprises around the world. As the third generation of solar cells, perovskite solar cells use perovskite-type organic metal halide semiconductors with ABX3 structure as light-absorbing materials. They have the advantages of high photoelectric conversion efficiency, low cost, lightness, strong light transmittance, good weak light effect, and flexible production methods. After fifteen years of development, the certified efficiency of single-junction perovskite solar cells has increased from the initial 3.8% to 26.7%, and its development speed is unprecedented. Compared with crystalline silicon solar cells, perovskite solar cells have advantages in material usage, process temperature, preparation difficulty, environmental protection, production cost and other aspects, and are expected to achieve large-scale commercial applications and replace traditional crystalline silicon solar cells. However, perovskite materials are easily decomposed under the influence of humidity, light, heat and other environmental factors, and have poor stability, which limits their commercial application. Summary of the invention

[0003] Based on this, the first aspect of the present application provides a method for preparing a perovskite solar cell, the purpose of which is to improve the stability of the perovskite solar cell. The technical solution is as follows:

[0004] A method for preparing a perovskite solar cell comprises the following steps:

[0005] forming a nickel oxide thin film on a transparent conductive glass;

[0006] forming a self-assembled monolayer on the nickel oxide film;

[0007] mixing glutathione, perovskite material and organic solvent to obtain a perovskite precursor solution;

[0008] coating the perovskite precursor solution on the self-assembled monolayer to form a modified perovskite active layer;

[0009] forming an electron transport layer on the modified perovskite active layer;

[0010] An electrode is formed on the electron transport layer.

[0011] A second aspect of the present application provides a perovskite solar cell, which is prepared by the preparation method as described above.

[0012] Compared with the traditional solution, this application has the following beneficial effects:

[0013] The present application adds glutathione to the perovskite precursor solution. The inventors of the present application have found through research that glutathione can affect the nucleation process and crystallization orientation of organic-inorganic hybrid perovskite crystals, and can also affect the chemical bonding between the perovskite active layer and the nickel oxide film modified by the self-assembly molecule, thereby affecting the stability of the perovskite active layer and its various photoelectric properties at the buried interface of the nickel oxide modified by the self-assembly molecule. Specifically, after adding glutathione, the perovskite crystals are preferentially oriented, the perovskite defects at the surface and grain boundaries of the perovskite crystals are integrated and passivated, the residual stress of the perovskite active layer is released, the perovskite active layer has self-repairing ability, can effectively reduce the degradation of the perovskite crystals under the influence of humidity, light, heat and other environments, and improve the quality of the perovskite active layer. At the same time, after adding glutathione, its distribution throughout the perovskite active layer and the surface interface can interact with the nickel oxide nanoparticles and self-assembly molecules at the buried interface, effectively adjust the charge extraction efficiency at the interface, and block the penetration of external water and oxygen into the perovskite active layer. In summary, the present application adds glutathione to the perovskite precursor solution, which can improve the stability of the perovskite solar cell. At the same time, the perovskite cell prepared in the present application also has good photoelectric efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0015] Figure 1 This is a schematic diagram of the structure of a perovskite solar cell according to Example 1;

[0016] Figure 2 1 are JV curves of the perovskite solar cells of Example 1 and Comparative Example 1;

[0017] Figure 3 is the JV curve of the perovskite solar cell of Example 2;

[0018] Figure 4 is the JV curve of the perovskite solar cell of Example 3;

[0019] Figure 5 is the JV curve of the perovskite solar cell of Example 4;

[0020] Figure 6 is the JV curve of the perovskite solar cell of Comparative Example 3;

[0021] Figure 7 is the JV curve of the perovskite solar cell of Comparative Example 4;

[0022] Figure 8 The following are the test results of the perovskite active layer of Example 1 and Comparative Example 1 under ultraviolet and ozone conditions;

[0023] Fig. 9 These are the stability test results of the unencapsulated perovskite solar cells of Example 1 and Comparative Example 1 under nitrogen conditions;

[0024] Fig.10 These are the stability test results of the unencapsulated perovskite solar cells of Example 2 and Comparative Example 2 under nitrogen conditions;

[0025] Fig.11 These are the stability test results of the unencapsulated perovskite solar cells of Example 1 and Comparative Example 1 under continuous ultraviolet light irradiation conditions;

[0026] Fig.12 The XRD diagram of the perovskite active layer before and after moisture-heat aging in Example 1;

[0027] Fig.13 The XRD diagram of the perovskite active layer before and after moisture-heat aging of Comparative Example 1;

[0028] Fig.14 XRD diagram of the perovskite active layer before and after high temperature aging in Example 1;

[0029] Fig.15 This is the XRD diagram of the perovskite active layer before and after high temperature aging in comparative example 1. DETAILED DESCRIPTION

[0030] The present application will be further described in detail below in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0032] the term

[0033] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0034] In the present application, "plurality", "multiple", "multiple times", "plurality", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0035] In this application, "optionally", "optional" and "optional" refer to optional, that is, to any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0036] In this application, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0037] In the present application, when referring to a numerical interval (i.e., a numerical range), unless otherwise specified, the optional numerical distribution within the above numerical interval is deemed to be continuous and includes the two numerical endpoints of the numerical range (i.e., the minimum value and the maximum value), and every numerical value between the two numerical endpoints.

[0038] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0039] In the present application, the percentage content, unless otherwise specified, refers to mass percentage for solid-liquid mixing and solid-solid mixing, and volume percentage for liquid-liquid mixing.

[0040] In this application, when it comes to percentage concentration, unless otherwise specified, it refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0041] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.

[0042] A first aspect of the present application provides a method for preparing a perovskite solar cell. In one embodiment, the method for preparing a perovskite solar cell comprises the following steps:

[0043] Step 1: Clean the transparent conductive glass.

[0044] In this embodiment, the transparent conductive glass is ITO glass, and the sheet resistance is 15Ω·(sq) -1 The transparent conductive glass was ultrasonically cleaned with deionized water, acetone, and isopropanol for 15 min in sequence, dried with nitrogen, and then treated under ultraviolet ozone conditions for 15 min.

[0045] Step 2: forming a nickel oxide (NiOx) thin film on the transparent conductive glass.

[0046] Optionally, forming a nickel oxide thin film on the transparent conductive glass comprises the following steps:

[0047] mixing water and nickel oxide powder to obtain a nickel oxide dispersion;

[0048] A nickel oxide dispersion is coated on a transparent conductive glass and annealed to form a nickel oxide film.

[0049] The water may be deionized water. After the nickel oxide powder is dispersed in the deionized water, ultrasonic dispersion may be performed to uniformly disperse the nickel oxide to obtain a nickel oxide dispersion. Optionally, the concentration of nickel oxide in the nickel oxide dispersion is 10 mg·mL -1 ~20mg·mL -1 For example, the concentration of nickel oxide in the nickel oxide dispersion is 10 mg mL -1 , 15mg·mL -1 , 20mg·mL -1 The ultrasonic time is 20min~60min. For example, the ultrasonic time is 20min, 40min, and 60min. Let it stand after ultrasonication and observe whether it is stratified before use. If there is no stratification, it can be used normally.

[0050] The method of applying the nickel oxide dispersion can be spin coating. Optionally, the spin coating speed is 3500 rpm to 4500 rpm. For example, the spin coating speed is 3500 rpm, 4000 rpm, 4500 rpm. The spin coating time is 20 s to 40 s. For example, the spin coating time is 20 s, 30 s, 40 s.

[0051] Optionally, the annealing temperature is 100° C. to 120° C. For example, the annealing temperature is 100° C., 110° C., or 120° C. The annealing time is 15 min to 25 min. For example, the annealing time is 15 min, 20 min, or 25 min.

[0052] Step 3: forming a self-assembled monolayer (SAM) on the nickel oxide film.

[0053] Optionally, the self-assembled monolayer includes [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), [4-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz), [4-(7 One or more of (4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl)phosphonic acid (DMAcPA), (2-(3,6-dibromo-9H-carbazole-9-yl)ethyl)phosphonic acid (Br-2PACz) and [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz).

[0054] Optionally, forming a self-assembled monolayer on the nickel oxide film comprises the following steps:

[0055] dissolving a self-assembled monomolecule in a first alcohol solvent to obtain a self-assembled monomolecule solution;

[0056] The self-assembled monomolecular solution is coated on the nickel oxide film, and first annealed to obtain a self-assembled monomolecular layer.

[0057] It is understandable that the step of post-processing the self-assembled monolayer is also included to remove unbound self-assembled molecules. The post-processing includes the following steps:

[0058] A second alcohol solvent is coated on the self-assembled monomolecular layer, and a second annealing is performed.

[0059] Optionally, the first alcohol solvent is selected from one or more of ethanol, isopropanol and propanol. The second alcohol solvent is selected from one or more of ethanol, isopropanol and propanol. Optionally, the first alcohol solvent and the second alcohol solvent are the same.

[0060] Optionally, the concentration of the self-assembled monomolecules in the self-assembled monomolecule solution is 1 mmol·L -1 ~3 mmol·L -1 For example, the concentration of self-assembled molecules in the self-assembled monomolecular solution is 1mmol·L -1 , 2mmol·L -1 , 3mmol·L -1 .

[0061] Optionally, the method of coating the self-assembled monomolecular solution on the nickel oxide film is spin coating. Optionally, the rotation speed of the spin coating is 3500rpm~4500rpm. For example, the rotation speed of the spin coating is 3500rpm, 4000rpm, 4500rpm. The time of the spin coating is 20s~40s. For example, the time of the spin coating is 20s, 30s, 40s.

[0062] Optionally, the temperature of the first annealing is 90° C. to 110° C. For example, the temperature of the first annealing is 90° C., 100° C., or 110° C. The time of the first annealing is 5 min to 15 min. For example, the time of the first annealing is 5 min, 10 min, or 15 min.

[0063] After the first annealing, the self-assembled monolayer was cooled to room temperature.

[0064] Optionally, the method of coating the second alcohol solvent on the self-assembled monolayer is spin coating, and optionally, the spin coating speed is 3500rpm~4500rpm. For example, the spin coating speed is 3500rpm, 4000rpm, 4500rpm. The spin coating time is 20s~40s. For example, the spin coating time is 20s, 30s, 40s.

[0065] Optionally, the temperature of the second annealing is 90° C. to 110° C. For example, the temperature of the second annealing is 90° C., 100° C., or 110° C. The time of the second annealing is 3 min to 10 min. For example, the time of the second annealing is 3 min, 5 min, 7 min, or 10 min.

[0066] After the second annealing, the self-assembled monolayer was cooled to room temperature.

[0067] Step 4: Mix glutathione (GSH), perovskite material (Perovskite) and organic solvent to obtain a perovskite precursor solution.

[0068] Optionally, the concentration of glutathione in the perovskite precursor solution is 0.1 mg·mL -1 ~5mg·mL -1 For example, the concentration of glutathione in the perovskite precursor solution is 0.1 mg·mL -1 , 0.5mg·mL -1 , 1mg·mL -1 , 1.5mg·mL -1 , 2mg·mL -1 , 2.5mg·mL -1 , 3mg·mL -1 , 3.5mg·mL -1 , 4mg·mL -1 , 4.5mg·mL-1 , 5mg·mL -1 .

[0069] Optionally, mixing glutathione, perovskite material and organic solvent comprises the following steps:

[0070] The glutathione and a portion of the organic solvent are mixed, stirred at a temperature of 50° C. to 70° C., and the remaining portion of the organic solvent and the perovskite material are added.

[0071] For example, the stirring temperature for mixing glutathione and a portion of the organic solvent includes, but is not limited to, 50°C, 60°C, and 70°C.

[0072] Experimental verification has shown that adding glutathione to the perovskite precursor solution can be used to regulate the crystallization dynamics of perovskite, stabilize the optically active phase of perovskite, and improve the stability and photoelectric efficiency of perovskite solar cells.

[0073] Optionally, the perovskite material is a crystalline material of ABX3 type structure, wherein A is a monovalent organic cation or an inorganic cation, B is a divalent metal cation, and X is a halogen anion. Further optionally, A is selected from methylamine, methylamidine or cesium ion, and B is selected from Pb 2+ Sn 2+ Or Ge 2+ , X is selected from Cl - Br - or I - Further optionally, the perovskite material is selected from one or more of PbI2, CsI, PbBr2, MABr, MACl and FAI.

[0074] Optionally, the total concentration of the perovskite material in the perovskite precursor solution is 1 mol·L -1 ~2mol·L -1 For example, the total concentration of the perovskite material in the perovskite precursor solution is 1 mol·L -1 , 1.5 mol·L -1 , 2mol·L -1 .

[0075] Optionally, the perovskite material includes PbI2, and its concentration in the perovskite precursor solution is 1.5M~2M. Optionally, the perovskite material includes CsI, and its concentration in the perovskite precursor solution is 0.05M~0.15M. Optionally, the perovskite material includes PbBr2, and its concentration in the perovskite precursor solution is 0.01M~0.05M. Optionally, the perovskite material includes MABr, and its concentration in the perovskite precursor solution is 0.01M~0.05M. Optionally, the perovskite material includes MACl, and its concentration in the perovskite precursor solution is 0.01M~0.05M. Optionally, the perovskite material includes FAI, and its concentration in the perovskite precursor solution is 1.2M~2M. Wherein, M represents mol·L -1 .

[0076] Optionally, the organic solvent is selected from one or more of a sulfone solvent and an amide solvent. The sulfone solvent may be dimethyl sulfoxide (DMSO). The amide solvent may be N,N-dimethylformamide (DMF).

[0077] Optionally, the organic solvent includes a sulfone solvent and an amide solvent, and mixing glutathione, a perovskite material and the organic solvent comprises the following steps:

[0078] Mixing the glutathione and the sulfone solvent, stirring at a temperature of 50° C. to 70° C., to obtain a glutathione solution;

[0079] mixing the glutathione solution and an amide solvent to obtain a mixed solution;

[0080] The perovskite material is added to the mixed solution.

[0081] Optionally, the volume ratio of the glutathione solution to the amide solvent is 1:(4-5).

[0082] Optionally, the stirring time is continued for 1 hour to 3 hours. After completion, the solution is filtered and the filtrate is collected to obtain a perovskite precursor solution.

[0083] Step 5: coating the perovskite precursor solution on the self-assembled monolayer to form a modified perovskite active layer.

[0084] Optionally, the method of coating the perovskite precursor solution on the self-assembled monolayer is spin coating. Take 40 μL~60 μL of the perovskite solution, first spin coat at low speed, then spin coat at high speed. Optionally, the rotation speed of the low-speed spin coating is 500rpm~1500rpm. For example, the rotation speed of the low-speed spin coating is 500rpm, 1000rpm, 1500rpm. The time of the low-speed spin coating is 5s~10s. For example, the time of the low-speed spin coating is 5s, 8s, 10s. The rotation speed of the high-speed spin coating is 4000rpm~5000rpm. For example, the rotation speed of the high-speed spin coating is 4000rpm, 4500rpm, 5000rpm. The time of the high-speed spin coating is 20s~40s. For example, the time of the high-speed spin coating is 20s, 30s, 40s.

[0085] After coating the perovskite precursor solution, the method further includes coating an anti-solvent.

[0086] Optionally, the anti-solvent is chlorobenzene.

[0087] Optionally, the method for coating the anti-solvent is spin coating, and the anti-solvent is added dropwise and spin-coated on the substrate coated with the perovskite solution 5s to 20s before the end of the spin coating.

[0088] Optionally, after coating the anti-solvent, annealing is performed to obtain a perovskite active layer. Optionally, the annealing temperature is 100°C to 150°C. For example, the annealing temperature is 100°C, 120°C, or 150°C. The annealing time is 10 min to 60 min. For example, the annealing time is 10 min, 30 min, or 60 min.

[0089] Step six: forming an interface regulation layer on the modified perovskite active layer.

[0090] Optionally, the material of the interface regulation layer includes PEABr. Forming the interface regulation layer on the modified perovskite active layer includes the following steps:

[0091] Dissolving PEABr in a solvent to obtain a PEABr solution;

[0092] The PEABr solution is coated on the modified perovskite active layer and annealed to obtain an interface regulation layer.

[0093] Optionally, the solvent includes one or more of isopropyl alcohol (IPA) and DMSO. For example, the solvent includes IPA and DMSO, and the volume ratio of IPA to DMSO is (180-220):1.

[0094] Optionally, in the PEABr solution, the concentration of PEABr is 0.5 mg mL -1 ~1.5mg·mL -1 For example, the concentration of PEABr is 0.5 mg mL-1 , 1mg·mL -1 , 1.5mg·mL -1 .

[0095] Optionally, the method of coating the PEABr solution on the modified perovskite active layer is spin coating. Optionally, the spin coating speed is 3500rpm~4500rpm. For example, the spin coating speed is 3500rpm, 4000rpm, 4500rpm. The spin coating time is 20s~40s. For example, the spin coating time is 20s, 30s, 40s.

[0096] Optionally, the annealing temperature is 90° C. to 110° C. For example, the annealing temperature is 90° C., 100° C., or 110° C. The annealing time is 5 min to 10 min. For example, the annealing time is 5 min, 8 min, or 10 min.

[0097] Step 7: forming an electron transport layer on the interface regulation layer.

[0098] In this embodiment, an interface regulation layer is formed. In other embodiments, the interface regulation layer may not be formed, and an electron transport layer may be directly formed on the modified perovskite active layer.

[0099] Optionally, the electron transport layer includes a first electron transport layer and a second electron transport layer stacked. The material of the first electron transport layer includes one or more of PCBM and C60. The material of the second electron transport layer includes BCP. For example, the first electron transport layer includes PCBM and C60, the second electron transport layer includes BCP, and forming the electron transport layer on the interface regulation layer includes the following steps:

[0100] Dissolving PCBM and C60 in a first solvent to obtain a mixed solution;

[0101] coating the mixed solution on the interface regulation layer to obtain a PCBM layer;

[0102] dissolving BCP in a second solvent to obtain a BCP solution;

[0103] The BCP solution is coated on the PCBM layer to obtain a BCP layer.

[0104] Optionally, the mass ratio of PCBM to C60 is (3-5):1. For example, the mass ratio of PCBM to C60 is 3:1, 4:1, 5:1. The total concentration of PCBM and C60 in the mixed solution is 20 mg·mL -1 ~30mg·mL -1 For example, the total concentration of PCBM and C60 in the mixed solution is 20 mg mL -1 , 25mg·mL-1 、30mg·mL -1 Optionally, the first solvent is chlorobenzene (CB).

[0105] Optionally, the method of coating the mixed solution on the interface regulation layer is spin coating. The spin coating speed is 2500rpm~3500rpm. For example, the spin coating speed is 2500rpm, 3000rpm, 3500rpm. The spin coating time is 20s~40s. For example, the spin coating time is 20s, 30s, 40s.

[0106] Optionally, the concentration of the BCP solution is 0.2 mg mL -1 ~0.8mg·mL -1 For example, the concentration of BCP solution is 0.2 mg mL -1 , 0.6mg·mL -1 , 0.8mg·mL -1 Optionally, the second solvent is isopropanol.

[0107] Optionally, the BCP solution is coated on the PCBM layer by spin coating. The spin coating speed is 4000 rpm to 6000 rpm. For example, the spin coating speed is 4000 rpm, 5000 rpm, 6000 rpm. The spin coating time is 20 s to 40 s. For example, the spin coating time is 20 s, 30 s, 40 s.

[0108] Step eight: forming an electrode on the electron transport layer.

[0109] Optionally, the electrode is a silver electrode, and the method of forming the silver electrode is evaporation.

[0110] Optionally, the thickness of the Ag electrode is 100 nm to 150 nm. For example, the thickness of the Ag electrode is 100 nm, 120 nm, or 150 nm.

[0111] The present application adds glutathione to the perovskite precursor solution. The inventors of the present application have found through research that glutathione can affect the nucleation process and crystallization orientation of organic-inorganic hybrid perovskite crystals, and can also affect the chemical bonding between the perovskite active layer and the nickel oxide film modified by the self-assembly molecule, thereby affecting the stability of the perovskite active layer and its various photoelectric properties at the buried interface of the nickel oxide modified by the self-assembly molecule. Specifically, after adding glutathione, the perovskite crystals are preferentially oriented, the perovskite defects at the surface and grain boundaries of the perovskite crystals are integrated and passivated, the residual stress of the perovskite active layer is released, the perovskite active layer has self-repairing ability, can effectively reduce the degradation of the perovskite crystals under the influence of humidity, light, heat and other environments, and improve the quality of the perovskite active layer. At the same time, after adding glutathione, its distribution throughout the perovskite active layer and the surface interface can interact with the nickel oxide nanoparticles and self-assembly molecules at the buried interface, effectively adjust the charge extraction efficiency at the interface, and block the penetration of external water and oxygen into the perovskite active layer. In summary, the present application adds glutathione to the perovskite precursor solution, which can improve the stability of the perovskite solar cell. At the same time, the perovskite cell prepared in the present application also has good photoelectric efficiency.

[0112] In addition, the above-mentioned preparation process is simple and has low requirements on the process environment, which enables the simple and repeatable preparation of high-quality and high-stability films and devices, and has broad prospects for promotion and application.

[0113] The second aspect of the present application provides a perovskite solar cell, which is prepared by the preparation method as described above. The perovskite solar cell prepared by the method of the present application still maintains more than 94% of the initial efficiency in an unpackaged state in a N2 atmosphere after 2000 hours.

[0114] The following is further described in conjunction with specific embodiments and comparative examples. The raw materials involved in the following specific embodiments and comparative examples, unless otherwise specified, can all be commercially available, the instruments used, unless otherwise specified, can all be commercially available, and the processes involved, unless otherwise specified, are all routinely selected by those skilled in the art.

[0115] Example 1

[0116] This embodiment provides a perovskite solar cell and a method for preparing the same, the steps are as follows:

[0117] Step 1, treating ITO conductive glass: clean the ITO conductive glass with a size of 20×20 mm with deionized water, acetone, and isopropanol ultrasonically for 15 minutes in sequence, blow dry the ITO conductive glass with nitrogen, and then treat it under ultraviolet ozone conditions for 15 minutes.

[0118] Step 2: Preparation of NiOx film: Add nickel oxide powder to deionized water in air at a concentration of 20 mg mL -1 , shake the dispersion for 1-2 minutes to disperse the particles, then ultrasonicate for 20 minutes to obtain a nickel oxide solution in which the particles are fully wetted with water. The nickel oxide solution is dropwise spin-coated on the cleaned ITO conductive glass at a speed of 4000 rpm for 30 seconds, and then annealed at 110°C for 20 minutes to obtain a NiOx film.

[0119] Step 3: Prepare the SAM layer: Under N2 atmosphere, dissolve 1 mmol of SAM molecules (Me-4PACz) in 1 mL of ethanol, stir thoroughly to obtain a SAM solution; drop the SAM solution onto the NiOx film by spin coating at a speed of 4000 rpm for 30 seconds, and then anneal at 100°C for 10 minutes to obtain a SAM layer. After the SAM layer is cooled to room temperature, drop ethanol onto the SAM layer by spin coating at a speed of 4000 rpm for 30 seconds, and then anneal at 100°C for 5 minutes.

[0120] Step 4. Prepare perovskite precursor solution: add 1 mg of glutathione to 1 mL of DMSO, stir at 60 ° C for 30 minutes to obtain a glutathione DMSO solution, take 0.2 mL of glutathione DMSO solution and 0.8 mL of DMF solution in a volume ratio of 1:4, mix to obtain 1 mL of a mixed solution, add PbI2 (1.78 M), CsI (0.09 M), PbBr2 (0.03 M), MABr (0.03 M), MACl (0.27 M) and FAI (1.61 M) to the mixed solution, stir at room temperature for two hours, and filter using a polytetrafluoroethylene (PTFE) filter with a pore size of 0.45 μm to obtain a perovskite precursor solution.

[0121] Step 5: Prepare the perovskite active layer: drop 50 μL of the perovskite precursor solution on the SAM layer, set the low speed to 1000 rpm for 5 seconds and the high speed to 5000 rpm for 40 seconds. After high-speed rotation for 20 seconds, drop 200 μL of the anti-solvent chlorobenzene on the rotating substrate at a uniform speed. After the end, anneal at 100 ° C for 30 minutes to obtain the perovskite active layer.

[0122] Step 6. Prepare the PEABr layer: Dissolve PEABr in a mixture of IPA and DMSO (volume ratio 200:1) at a concentration of 1 mg mL -1 The PEABr solution was dynamically spin-coated on the perovskite active layer at a speed of 4000 rpm for 30 s, and then annealed at 100 °C for 5 min.

[0123] Step 7: Prepare the PCBM layer: dissolve 25 mg of PCBM and C60 (mass ratio 4:1) in 1 mL of chlorobenzene solution, stir evenly, and then spin-coat the mixed solution on the PEABr layer at a speed of 3000 rpm for 30 seconds to obtain the PCBM layer.

[0124] Step 8. Prepare the BCP layer: Dissolve BCP in isopropanol at a concentration of 0.5 mg mL -1 , a BCP solution was obtained, which was stirred at 70°C for 2 hours before use, and spin-coated on the PCBM layer at a rotation speed of 5000 rpm for 30 seconds to obtain a BCP layer.

[0125] Step 9: Prepare the Ag electrode: Use vacuum thermal evaporation to deposit a 100nm thick Ag electrode on the BCP layer to complete the preparation of the perovskite solar cell. The structure of the perovskite solar cell is as follows: Figure 1 As shown, the perovskite solar cell 100 includes an ITO conductive glass 11, a NiOx film 12, a SAM layer 13, a perovskite active layer 14, a PEABr layer 15, a PCBM layer 16, a BCP layer 17 and an Ag electrode 18 which are stacked in sequence.

[0126] Example 2

[0127] This embodiment provides a perovskite solar cell and a method for preparing the same. The main difference from Embodiment 1 is that step three is different, specifically:

[0128] Step 3: Prepare the SAM layer: Under N2 atmosphere, dissolve 1 mmol of SAM molecules (4PADBC) in 1 mL of ethanol, stir thoroughly to obtain a SAM solution; drop the SAM solution onto the NiOx film by spin coating at a speed of 4000 rpm for 30 seconds, and then anneal at 100°C for 10 minutes to obtain a SAM layer. After the SAM layer is cooled to room temperature, drop ethanol onto the SAM layer by spin coating at a speed of 4000 rpm for 30 seconds, and then anneal at 100°C for 5 minutes.

[0129] Example 3

[0130] This embodiment provides a perovskite solar cell and a method for preparing the same. The main difference from Embodiment 1 is that step 4 is different, specifically:

[0131] Step 4. Prepare perovskite precursor solution: add 5 mg of glutathione to 1 mL of DMSO, stir at 60 ° C for 30 minutes to obtain a glutathione DMSO solution, take 0.2 mL of glutathione DMSO solution and 0.8 mL of DMF solution in a volume ratio of 1:4, mix to obtain 1 mL of a mixed solution, add PbI2 (1.78 M), CsI (0.09 M), PbBr2 (0.03 M), MABr (0.03 M), MACl (0.27 M) and FAI (1.61 M) to the mixed solution, stir at room temperature for two hours, and filter using a polytetrafluoroethylene (PTFE) filter with a pore size of 0.45 μm to obtain a perovskite precursor solution.

[0132] Example 4

[0133] This embodiment provides a perovskite solar cell and a method for preparing the same. The main difference from Embodiment 1 is that step three is different, specifically:

[0134] Step 3: Prepare the SAM layer: Under N2 atmosphere, dissolve 3 mmol of SAM molecules (Me-4PACz) in 1 mL of ethanol, stir thoroughly to obtain a SAM solution; drop the SAM solution onto the NiOx film by spin coating at a speed of 4000 rpm for 30 seconds, and then anneal at 100°C for 10 minutes to obtain a SAM layer. After the SAM layer is cooled to room temperature, drop ethanol onto the SAM layer by spin coating at a speed of 4000 rpm for 30 seconds, and then anneal at 100°C for 5 minutes.

[0135] Comparative Example 1

[0136] This comparative example provides a perovskite solar cell and a preparation method thereof, which is mainly different from Example 1 in that step 4 is different, specifically:

[0137] Step 4. Prepare perovskite precursor solution: Add PbI2 (1.78 M), CsI (0.09 M), PbBr2 (0.03 M), MABr (0.03 M), MACl (0.27 M) and FAI (1.61 M) to 1 mL of a mixed solution of DMF and DMSO (the volume ratio of DMF to DMSO is 4:1). After stirring at room temperature for two hours, filter using a polytetrafluoroethylene (PTFE) filter with a pore size of 0.45 μm to obtain a perovskite precursor solution.

[0138] Comparative Example 2

[0139] This comparative example provides a perovskite solar cell and a preparation method thereof, which is mainly different from Example 2 in that step 4 is different, specifically:

[0140] Step 4. Prepare perovskite precursor solution: Add PbI2 (1.78 M), CsI (0.09 M), PbBr2 (0.03 M), MABr (0.03 M), MACl (0.27 M) and FAI (1.61 M) to 1 mL of a mixed solution of DMF and DMSO (the volume ratio of DMF to DMSO is 4:1). After stirring at room temperature for two hours, filter using a polytetrafluoroethylene (PTFE) filter with a pore size of 0.45 μm to obtain a perovskite precursor solution.

[0141] Comparative Example 3

[0142] This comparative example provides a perovskite solar cell and a preparation method thereof, which is mainly different from Example 1 in that step 2 is omitted, a nickel oxide film is no longer prepared, and the hole transport layer is a self-assembled monolayer.

[0143] Comparative Example 4

[0144] This comparative example provides a perovskite solar cell and a preparation method thereof, which is mainly different from Example 1 in that step three is omitted, a self-assembled monolayer is no longer prepared, and the hole transport layer is a nickel oxide film.

[0145] Performance comparison

[0146] Figure 2 : are the JV curves of the perovskite solar cells prepared in Example 1 and Comparative Example 1, Figure 3 : is the JV curve of the perovskite solar cell prepared in Example 2 and Comparative Example 2. Figure 2 and Figure 3 It can be seen that the photoelectric conversion efficiency of perovskite solar cells without the addition of glutathione (w / o GSH, without GSH) is significantly lower than that of perovskite solar cells with the addition of glutathione (w / GSH, with GSH). After adding glutathione, the improvement of photovoltaic parameters such as open circuit voltage, short circuit current and fill factor of perovskite solar cells also fully demonstrates that glutathione is beneficial to the photoelectric efficiency of perovskite solar cells.

[0147] Figure 4 is the JV curve of the perovskite solar cell prepared in Example 3, Figure 5 This is the JV curve of the perovskite solar cell prepared in Example 4. Figure 4 and Figure 5 It can be seen that after adding glutathione, as the concentration of glutathione changes within a certain range and the concentration of self-assembled molecules changes within a certain range, the perovskite solar cell can maintain a high photoelectric conversion efficiency.

[0148] Figure 6is the JV curve of the perovskite solar cell prepared in Comparative Example 3, Figure 7 : is the JV curve of the perovskite solar cell prepared in Comparative Example 4. Figure 6 and Figure 7 It can be seen that the combination of NiOx thin film and SAM layer has a positive effect on improving the photoelectric efficiency of perovskite solar cells.

[0149] Figure 8 The following test results of the perovskite active layer prepared in Example 1 and Comparative Example 1 under ultraviolet and ozone conditions are shown. The perovskite active layer without glutathione and with glutathione added is placed under strong ultraviolet and ozone conditions. The macroscopic morphology of the perovskite active layer is photographed with a high-resolution camera every 3 minutes. The first column is the macroscopic morphology of the perovskite active layer of Example 1, and the second column is the macroscopic morphology of the perovskite active layer of Comparative Example 1. It can be observed that the morphology of the perovskite active layer without glutathione added in the second column changes significantly after 18 minutes and begins to degrade. However, the perovskite active layer with glutathione added under the same conditions performs well. Therefore, the perovskite film with glutathione added shows better stability under ultraviolet and ozone conditions than the perovskite film without glutathione added.

[0150] Fig. 9 The stability test results of the unencapsulated perovskite solar cells prepared in Example 1 and Comparative Example 1 under nitrogen conditions are shown. The unencapsulated perovskite solar cells with and without glutathione added are placed in a nitrogen environment. After 2000 hours, the photoelectric conversion efficiency of the perovskite solar cell with glutathione added retains more than 94% of the initial efficiency, but the battery without glutathione added only retains 48.7% of the initial efficiency after being stored for about 900 hours.

[0151] Fig.10 The stability test results of the unencapsulated perovskite solar cells prepared in Example 2 and Comparative Example 2 under nitrogen conditions are shown. The unencapsulated perovskite solar cells with and without glutathione added are placed in a nitrogen environment. After about 900 hours, the photoelectric conversion efficiency of the perovskite solar cell with glutathione added retains 88.1% of the initial efficiency, but the cell without glutathione added only retains 70.9% of the initial efficiency.

[0152] Fig.11 The stability test results of the unencapsulated perovskite solar cells prepared in Example 1 and Comparative Example 1 under continuous ultraviolet light conditions are shown. The unencapsulated perovskite solar cells with and without glutathione added are placed in a continuous ultraviolet light environment. Under the same test conditions, the perovskite solar cells with glutathione added retain a higher initial efficiency, indicating that glutathione achieves a synergistic improvement in battery efficiency and stability.

[0153] The unencapsulated perovskite solar cells without or with glutathione were exposed to an atmospheric environment with a humidity of 85% and a temperature of 28°C for 6 days for moisture-heat aging treatment, and were exposed to a nitrogen environment continuously heated at 100°C for high-temperature aging treatment. The stability of the perovskite active layer was studied by XRD testing. Fig.12 The XRD diagram of the perovskite active layer before and after moisture-heat aging in Example 1 is shown in FIG. Fig.13 The XRD diagram of the perovskite active layer before and after moisture-heat aging in comparative example 1 is shown in FIG. Fig.14 The XRD diagram of the perovskite active layer before and after high temperature aging in Example 1 is shown in FIG. Fig.15 The XRD diagram of the perovskite active layer before and after high temperature aging in comparative example 1. It can be seen that in an atmospheric environment with a humidity of 85% and a temperature of 28°C, after 6 days of aging treatment, the XRD peak of PbI2 at 12.7° in the perovskite active layer without the addition of glutathione increased significantly, indicating the rapid decomposition of the perovskite active layer. However, under the same conditions, it can be observed that after adding glutathione to the perovskite active layer, the XRD peak of PbI2 in the perovskite active layer after aging is still negligible. The same trend of change is also shown in the XRD spectrum of the perovskite active layer continuously heated at 100°C. This shows that glutathione effectively inhibits the decomposition of the perovskite active layer, reduces the excess PbI2 at the boundary, and eliminates the harmful effects of PbI2 on the stability of perovskite.

[0154] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0155] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a perovskite solar cell, characterized in that: The following steps are involved: forming a nickel oxide film on the transparent conductive glass, wherein the nickel oxide film comprises nickel oxide nanoparticles; A self-assembled monolayer is formed on the nickel oxide film, wherein the self-assembled monolayer includes one or more of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid, [4-(9H-carbazole-9-yl)butyl]phosphonic acid, (4-(2,7-dibromo-9,9-dimethylacridine-10(9H)-yl)butyl)phosphonic acid, (2-(3,6-dibromo9H-carbazole-9-yl)ethyl)phosphonic acid and [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid; Mixing glutathione, a perovskite material and an organic solvent to obtain a perovskite precursor solution, wherein the perovskite material is a crystalline material with an ABX3 structure, wherein A is a monovalent organic cation or an inorganic cation, B is a divalent metal cation, and X is a halogen anion; coating the perovskite precursor solution on the self-assembled monolayer to form a modified perovskite active layer; forming an electron transport layer on the modified perovskite active layer; An electrode is formed on the electron transport layer.

2. The method for preparing a perovskite solar cell according to claim 1, characterized in that: The concentration of glutathione in the perovskite precursor solution is 0.1 mg·mL -1 ~5mg·mL -1 .

3. The method for preparing a perovskite solar cell according to claim 2, characterized in that: Mixing glutathione, perovskite material and organic solvent comprises the following steps: The glutathione and a portion of the organic solvent are mixed, stirred at a temperature of 50° C. to 70° C., and the remaining portion of the organic solvent and the perovskite material are added.

4. The method for preparing a perovskite solar cell according to claim 1, characterized in that: A is selected from methylamine, methylamidine or cesium ion, and B is selected from Pb 2+ Sn 2+ Or Ge 2+ , X is selected from Cl - Br - or I - .

5. The method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The total concentration of the perovskite material in the perovskite precursor solution is 1 mol·L -1 ~2mol·L -1 .

6. The method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The organic solvent is selected from one or more of sulfone solvents and amide solvents.

7. The method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: After coating the perovskite precursor solution, the method further includes coating an anti-solvent.

8. The method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The electron transport layer includes a first electron transport layer and a second electron transport layer which are stacked.

9. The method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The method also includes forming an interface regulating layer between the modified perovskite active layer and the electron transport layer.

10. A perovskite solar cell, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Charge transport layer structure of perovskite / crystalline silicon laminated solar cell and perovskite / crystalline silicon laminated solar cell

    CN114824094A

  • Hole transport layer prepared from mesoporous nickel oxide and self-assembly material, perovskite solar cell formed by hole transport layer and preparation method of perovskite solar cell

    CN117241640A